Adaptation of e-health impact questionnaire into Turkish: a validity and reliability study - Kafes, Mustafa; Kaya, Serife Didem (Frontiers in Digital Health, 2025)
Introductione-Health refers to the use of information and communication technologies (ICT) for health-related services. e-Health aims to distribute scarce resources to areas in need more efficiently and to reduce the cost of health care delivery. However, although the health information on the web-based internet is sometimes provided by specialist and similar health professionals, it should be stated that the opposite can also happen. In this study, it is aimed to adapt the e-health impact questionnaire, which was developed to allow comparison of two or more websites containing health information, into Turkish, and to conduct a reliability and validity study.MethodsThis study is in methodological research design. The first part consists of items containing “general attitudes towards health-related websites”. This section consists of 11 items, two of which are sub-dimensions. The second part consists of items containing “opinions about the website reviewed”. This section contains a total of 26 items, three of which are sub-dimensions. SPPS and AMOS package programs were used in the analysis of the data.ResultsIt is seen that 18% of the individuals participating in the study (n = 388) were male and 82% were female. While 85.1% of them are studying or have studied at the undergraduate level, 14.9% of them are in postgraduate education. Part 1 of the questionnaire are as follows: (χ2/df) = 3.64 (χ2 = 156,843/df = 43); RMSEA = 0.08; GFI = 0.93; AGFI = 0.89; CFI = 0.92; TLI = 0.90; PGFI = 0.61 and NFI = 0.90. Part 2 are as follows: 4.81 (χ2/df) (χ2 = 1423.541/df = 296); RMSEA = 0.099; GFI = 0.75; AGFI = 0.70; CFI = 0.82; TLI = 0.80; PGFI = 0.63 and NFI = 0.79.ConclusionThis study suggests using this instrument to survey perceptions of e-health technology in Turkish people.